Screen-based sedentary behavior and physical activity levels of undergraduate students in Dipolog City during the COVID-19 Pandemic - Redulla, Jericho P. 2000-
Digital technology has become the common cause of sedentary behavior in recent times and Philippines is one of the countries with the highest screen time usage through mobile devices alone. Alongside that, the COVID-19 pandemic restrictions have caused limitations in exercise options as it can only be done at home, which poses a general problem in terms of exercise space and access to equipment. With this information, the aim of this study is to provide a statistical description regarding screen time and physical activity levels towards a specific population locale, which in this case is the undergraduate student population in Dipolog City. This study conducted a descriptive research design. The research used a Google forms survey which consisted of the personal background, the Sedentary Behaviour Questionnaire (SBQ) and the Global Physical Activity Questionnaire (GPAQ). According to the results, seven out of eight undergraduate students are sedentary in terms of their screen time and about six to seven out of ten students are considered physically inactive. Furthermore, the results showed that the male student population were more physically active than the female population, especially in terms of the fitness and recreation activities. Further studies must be conducted with a wider scope to represent the results to a more general population. Future studies should also include the present rate of screen-based sedentary behavior and physical activity levels of any target population.